The Performance Characteristics of The Low Head Cross Flow Turbine Using Nozzle Roof Curvature Radius Centered on Shaft Axis - Sutikno, Djoko; Soenoko, Rudy; Soeparman, Sudjito; Wahyudi, Slamet; Azmi, M. Azham (International Journal of Integrated Engineering, 2019)
The experimental study was intended to investigate performance characteristics of three cross  flow turbine model using nozzle roof curvature radius centered on shaft axis designed on the same flow rate, runner diameter and rotational speed which with each model having different runner width as well as its nozzle entry arc. The nozzle and runner width were designed as the fuction of the nozzle entry arc, the shorter pair of runner-nozzle the larger nozzle entry arc and vise versa. The nozzle entry arcs used in this experimental study were 75o, 90o and 120o. In addition, the three models having equal cross sectional area of nozzle entry. The three  turbine nozzles  were designed having roof curvature radius centered on shaft axis. The such nozzle roof curvature were expected to be able to deliver water in the better direction as well as its flow condition as the water entering the tubine runner. The experimental test rig consisted of the three turbine models, pump, piping systems, magnetic flow meter, and tachometer. The Flow rates, entered the turbine, supplied by the pump were measured by the magnetic flow meter.  The power generated on the turbine shaft was determined by measuring the torsion forces detected by using a spring balance, and turbine speeds were detected by a hand held tachometer. The turbine performance characteristics are shown by the relation of efficiency versus flow rate, head, and specific speed; as well as the relation of efficiency versus velocity ratio and speed ratio. The velocity ratio was the ratio of runner pheripheral velocity to water jet velocity  entering  the runner; the speed ratio was the ratio of runner speed to water jet speed entering the runner. The results of the study indicate that best efficiency points increase as the nozzle entry arc decreases or on the other hand best effisiency points decrease as the nozzle entry arc increases. The results shows that the cross flow turbine using 75 and 90 degree entry arcs indicate efficiency and power higher than that of turbine with 120 degree nozzle entry arc.